Long non-coding RNA regulation of reproduction and development - Taylor, David H.; Chu, Erin Tsi-Jia; Spektor, Roman; Soloway, Paul D. (Molecular reproduction and development, 2015)
SUMMARY Noncoding RNAs (ncRNAs) have long been known to play vital roles in eukaryotic gene regulation. Studies conducted over a decade ago revealed that maturation of spliced, polyadenylated coding mRNA occurs by reactions involving small nuclear RNAs and small nucleolar RNAs; mRNA translation depends on activities mediated by transfer RNAs and ribosomal RNAs, subject to negative regulation by micro RNAs; transcriptional competence of sex chromosomes and some imprinted genes is regulated in cis by ncRNAs that vary by species; and both small‐interfering RNAs and piwi‐interacting RNAs bound to Argonaute‐family proteins regulate post‐translational modifications on chromatin and local gene expression states. More recently, gene‐regulating noncoding RNAs have been identified, such as long intergenic and long noncoding RNAs (collectively referred to as lncRNAs)—a class totaling more than 100,000 transcripts in humans, which include some of the previously mentioned RNAs that regulate dosage compensation and imprinted gene expression. Here, we provide an overview of lncRNA activities, and then review the role of lncRNAs in processes vital to reproduction, such as germ cell specification, sex determination and gonadogenesis, sex hormone responses, meiosis, gametogenesis, placentation, non‐genetic inheritance, and pathologies affecting reproductive tissues. Results from many species are presented to illustrate the evolutionarily conserved processes lncRNAs are involved in. Mol. Reprod. Dev. 82: 932–956, 2015. © 2015 Wiley Periodicals, Inc.